2015
DOI: 10.1016/j.jnucmat.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Screening of advanced cladding materials and UN–U3Si5 fuel

Abstract: In the aftermath of Fukushima, a focus of the DOE-NE Advanced Fuels Campaign has been the development of advanced nuclear fuel and cladding options with the potential for improved performance in an accident. Uranium dioxide (UO 2) fuels with various advanced cladding materials were analyzed to provide a reference for cladding performance impacts. For advanced cladding options with UO 2 fuel, most of the cladding materials have some reactivity and discharge burn-up penalty (in GWd/t). Silicon carbide is one exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Due to the much higher thermal conductivity, the temperature in the U3Si2 fuel is expected to be flatter (and lower in center) than that in UO2 fuel. Quantitative results can be obtained with the empirical formulae (8) and (9), and the temperature at the surface of fuels. This conclusion is verified by multi-physics coupling analysis recently [33].…”
Section: Radial Distributions Of Fuel Temperaturementioning
confidence: 99%
“…Due to the much higher thermal conductivity, the temperature in the U3Si2 fuel is expected to be flatter (and lower in center) than that in UO2 fuel. Quantitative results can be obtained with the empirical formulae (8) and (9), and the temperature at the surface of fuels. This conclusion is verified by multi-physics coupling analysis recently [33].…”
Section: Radial Distributions Of Fuel Temperaturementioning
confidence: 99%
“…These preliminary analyses were performed to provide initial insight into the possible improvements that ATF concepts could provide and to identify issues with respect to modeling ATF concepts. In addition to these scoping studies, screening studies were performed [10] and a common methodology and set of performance metrics were developed to compare and support prioritizing ATF concepts [11].…”
Section: Progression Of Atf Analysesmentioning
confidence: 99%
“…This resulted in the UO 2 mass increasing by 18.5%. The reduction in cladding thickness is based on previous reactor physics assessments of FeCrAl cladding in PWRs in which it was determined that maintaining operational cycle lengths was best accomplished through a small increase in batchaverage enrichment and reduction of the cladding thickness to about half of the nominal thickness [10,26,27]. Recent neutronics studies found similar results for BWRs as well; however, the studies suggest reducing both the cladding and channel box thicknesses by about 50% [28,29].…”
Section: Fuel and Cladding Geometrymentioning
confidence: 99%
“…2 Science and Technology of Nuclear Installations However, UN chemically reacts with water [8], especially at high temperature. Additional shielding material UN/U 3 Si 5 has been studied to overcome the defect [9]. But a problem still exists, which is the determination of the percentage of U 3 Si 5 to prevent the fuel from reacting with water in an accident condition.…”
Section: Introductionmentioning
confidence: 99%